Investigating Impact of US, Europe, Frontier and BRIC Stock Markets on Indian Financial Stress Index - Amanjot Singh; Manjit Singh (Journal of Banking and Financial Economics)
The emerging markets are slowly opening up their respective fi nancial markets to foreign investments, thereby making the latter markets more sensitive to cross-market information transmissions. There are different transmission mechanisms ranging from trade related to fi nancial linkages. However, statistically, both price discovery and conditional volatility act as transmission mechanisms, whereby information in one stock market has an impact on another. In this regard, the present study attempts to empirically analyse the impact of global information transmissions, i.e., stock market returns and conditional volatility on overall Indian fi nancial stress and its various sub-components by employing different econometric models comprising Johanson Cointegration, Vector Autoregression and its various counterparts, Component GARCH (1,1) model and multivariate OLS regression models ranging from October 2003 to October 2014. The study fi rstly constructed Indian fi nancial stress index owing to non-existence of a standardised index. The results reported that the one month lagged returns in the BRIC stock markets have an impact on the fi nancial stress index of India. The stress in the Indian fi nancial system responds statistically signifi cantly to the Brazilian and Chinese market returns, with a greater degree of integration after two months. A statistically signifi cant impact of the shortrun volatility has also been observed running from the European markets to the Indian fi nancial system contemporaneously. Furthermore, unexpected volatility in the BRIC markets also has an impact on the Indian fi nancial stress contemporaneously as well as dynamically. The present study provides an insight to the international investors regarding the response of Indian fi nancial system and its sub-components toward global information transmissions.